Structure of the Sac3 RNA-binding M-region in the Saccharomyces cerevisiae TREX-2 complex. Issue 9 (15th March 2017) - Gordon, James M. B.; Aibara, Shintaro; Stewart, Murray
Abstract: Transcription-export complex 2 (TREX-2, or THSC) facilitates localization of actively transcribing genes such as GAL1 to the nuclear periphery, contributes to the generation of export-competent mRNPs and influences gene expression through interactions with Mediator. TREX-2 is based on a Sac3 scaffold to which Thp1, Sem1, Cdc31 and Sus1 bind and consists of three modules: the N-region (Sac3 ∼1-100 ), which binds mRNA export factor Mex67:Mtr2; the M-region, in which Thp1 and Sem1 bind to Sac3 ∼100-550 ; and the CID region in which Cdc31 and two Sus1 chains bind to Sac3 ∼720-805 . Although the M-region of Sac3 was originally thought to encompass residues ∼250-550, we report here the 2.3Å resolution crystal structure of a complex containing Sac3 residues 60–550 that indicates that the TPR-like repeats of the M-region extend to residue 137 and that residues 90–125 form a novel loop that links Sac3 to Thp1. These new structural elements are important for growth and mRNA export in vivo . Although deleting Sac3 residues 1–90 produced a wild-type phenotype, deletion of the loop as well generated growth defects at 37°C, whereas the deletion of residues 1–250 impaired mRNA export and also generated longer lag times when glucose or raffinose was replaced by galactose as the carbon source.